Transesterification Reaction on Biodiesel Production from Bintaro Oil (Cerbera mangas L.) from Moluccas Island - I W. Sutapa; A. Bandjar; H. Tehubijuluw; I. S. Ely; A. Kamari; C. Baskar; I N. Sudiana; L. O. Kadidae (Faculty Mathematics and Natural Sciences, Halu Oleo University, 2025)
Research on the conversion of bintaro seed oil (Cerbera manghas L.) into biodiesel has been conducted utilizing a KOH catalyst. The biodiesel synthesis involved two reaction stages: esterification and transesterification. The esterification process was executed with a 1.25% H2SO4 (1 M) catalyst, utilizing a methanol-to-oil ratio of 1:9, at a temperature range of 60-65°C for a duration of 2 hours. Following the separation of methanol and triglycerides, transesterification proceeded with a methanol ratio of 1:12, which had previously reacted with KOH catalyst at varying weight percentages of 0.2%, 0.3%, 0.5%, 1%, and 1.5%. The transesterification reaction was conducted over a period of 2 hours at a temperature of 60-65°C. The optimal weight percentage of KOH catalyst identified for the transesterification reaction in the synthesis of biodiesel from bintaro seed oil was determined to be 0.3% KOH catalyst. The resultant biodiesel was subsequently characterized using Fourier Transform Infrared Spectroscopy (FT-IR) and Gas Chromatography-Mass Spectrometry (GC-MS). Physical property tests of the biodiesel fuel, conducted in accordance with ASTM methods, yielded a specific density of 0.8878 g/cm³, a kinematic viscosity of 6 mm²/s, a flash point of 132.5°C, and a pour point of 9°C.